2008
DOI: 10.1534/genetics.108.090449
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Spectral Tuning in the Red- and Green-Sensitive (M/LWS) Pigments in Vertebrates

Abstract: Vertebrate vision is mediated by five groups of visual pigments, each absorbing a specific wavelength of light between ultraviolet and red. Despite extensive mutagenesis analyses, the mechanisms by which contemporary pigments absorb variable wavelengths of light are poorly understood. We show that the molecular basis of the spectral tuning of contemporary visual pigments can be illuminated only by mutagenesis analyses using ancestral pigments. Following this new principle, we derive the ''five-sites'' rule tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 35 publications
(49 reference statements)
10
116
0
Order By: Relevance
“…With reference to M/LWS, in which five sites are major determinants of optimum light sensitivity (λ max ) (12), tuna has the same amino acids as medaka and stickleback (S, H, Y, T, and A) ( Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to M/LWS, in which five sites are major determinants of optimum light sensitivity (λ max ) (12), tuna has the same amino acids as medaka and stickleback (S, H, Y, T, and A) ( Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many fish species have two copies of SWS2 genes, consistent with the concept that an ancient duplication occurred and each copy has been retained for a long time. Previous studies have accumulated molecular information on opsins, focusing on the residues surrounding the retinal-binding pocket (10)(11)(12).…”
mentioning
confidence: 99%
“…Given that commonality, what cone pigments may have been present in the retinas of the early eutherians? Sequence comparisons of cone opsin genes have suggested that the ancestral mammalian pigments drawn from these two gene families peaked in the UV, at about 360 nm (Hunt et al 2001), and in the long wavelengths at 560 nm (Yokoyama et al 2008). Assuming the visual pigment chromophore of early mammals was 11-cis-retinal, the same as that of contemporary mammals, the cone pigments of early eutherian mammals would have had absorption properties similar to those sketched at the bottom of figure 1.…”
Section: (A) Monotremes and Marsupialsmentioning
confidence: 94%
“…In some cases models have been shown to successfully predict a visual pigment's λ max . Some examples include experimental verifications of the "five-sites rule" (Yokoyama and Radlwimmer, 1998;Yokoyama et al , 2008b) and the effect of SWS1 substitutions of large effect that cause this pigment to shift from the violet to the UV region in birds (Ödeen et al, 2009;Hauser et al, 2014). However, predicting λ max from opsin sequence can be far from simple and highly dependent on genetic background.…”
Section: From Opsin Genes To Spectral Tuningmentioning
confidence: 99%